2021
DOI: 10.1002/lt.25963
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Disease‐Specific Health‐Related Quality of Life of Pediatric Liver Transplant Recipients During Immunosuppression Withdrawal

Abstract: Long-term immunosuppression (IS) leads to systemic complications affecting health-related quality of life (HRQOL) in pediatric liver transplantation (LT) recipients. We serially assessed HRQOL using the PedsQL Generic and Multidimensional Fatigue Scales and Family Impact and Transplant Modules as part of a multicenter prospective immunosuppression withdrawal (ISW) trial between 2012 and 2018. Participants received a primary LT ≥4 years before the study and were on stable IS with normal liver tests and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[5,6] Furthermore, a decrease in IS is a priority for patients and families and has been associated with an improvement in transplantspecific health-related quality of life over time. [7] Our results underscore the importance of performing a surveillance liver biopsy prior to considering IS minimization and continuing to follow these patients with surveillance biopsies over time. We continue to recommend repeat surveillance biopsies every 5 years for all patients to monitor the health of the graft and identify subclinical inflammation or injury.…”
Section: Discussionmentioning
confidence: 55%
“…[5,6] Furthermore, a decrease in IS is a priority for patients and families and has been associated with an improvement in transplantspecific health-related quality of life over time. [7] Our results underscore the importance of performing a surveillance liver biopsy prior to considering IS minimization and continuing to follow these patients with surveillance biopsies over time. We continue to recommend repeat surveillance biopsies every 5 years for all patients to monitor the health of the graft and identify subclinical inflammation or injury.…”
Section: Discussionmentioning
confidence: 55%
“…4,[8][9][10][11]13,14, An update search returned 318 unique reports, of which three were screened in full text and only one was included. 12 Two iterations of backward and forward citation searching on included records yielded further 1188 records, of which nine were screened in full text and four [43][44][45][46] were included. Owing to cohort overlap or multiple reports on the same study (Table S2), the 35 included reports were found to cover 17 independent studies with extractable pre-withdrawal time data for meta-analysis (Table 1).…”
Section: Results Of the Search And Study Characteristicsmentioning
confidence: 99%
“…Thus, minimization and if possible, even withdrawal of these medications is currently the guiding principle of designing individualized immunosuppression protocols worldwide. If achieved, this immunosuppression-free state has been proven to reduce the metabolic syndrome risks and other attendant side effects and also improve overall quality of life [5,7,8].…”
Section: Discussionmentioning
confidence: 99%